Multi-layer pre-vascularized magnetic cell sheets for bone regeneration - Silva, Ana S. (2020)
The lack of effective strategies to produce vascularized 3D bone transplants in vitro, hampers the development of thick-constructed bone, limiting the translational of lab-based engineered system to clinical practices. Cell sheet (CS) engineering techniques provide an excellent microenvironment for vascularization since the technique can maintain the intact cell matrix, crucial for angiogenesis. In an attempt to develop hierarchical vascularized 3D cellular constructs, we herein propose the construction of stratified magnetic responsive heterotypic CSs by making use of iron oxide nanoparticles previously internalized within cells. Magnetic force-based CS engineering allows for the construction of thick cellular multilayers. Results show that osteogenesis is achieved due to a synergic effect of human umbilical vein endothelial cells (HUVECs) and adipose-derived stromal cells (ASCs), even in the absence of osteogenic differentiating factors. Increased ALP activity, matrix mineralization, osteopontin and osteocalcin detection were achieved over a period of 21 days for the heterotypic CS conformation (ASCs/HUVECs/ASCs), over the homotypic one (ASCs/ASCs), corroborating our findings. Moreover, the validated crosstalk between BMP-2 and VEGF releases triggers not only the recruitment of blood vessels, as demonstrated in an in vivo CAM assay, as well as the osteogenesis of the 3D cell construct. The in vivo angiogenic profile also demonstrated preserved human vascular structures and human cells showed the ability to migrate and integrate within the chick vasculature.